Click to enter: activation of oligo-arginine cell-penetrating peptides by bioorthogonal tetrazine ligations - Bode, Saskia A. (Royal Society of Chemistry, 2018)

(untitled) (Chem Sci)
Cell-penetrating peptides are able to transport a wide variety of cargo across cell membranes. Although promising, they are not often considered for therapeutic purposes as they lack controllable activity and cell selectivity. We have developed an activation strategy based on a split octa-arginine cell-penetrating peptide (CPP) that can be activated by means of bioorthogonal ligation. To this end we prepared two non-penetrating tetra-arginine halves, functionalized either with a tetrazine or with a complementary bicyclo[6.1.0]nonyne (BCN) group. We demonstrate that an active octa-arginine can be reconstituted in situ upon mixing the complementary split peptides. The resulting activated peptide is taken up as efficiently as the well-established cell-penetrating peptide octa-arginine. The activation of the oligo-arginines can also be achieved using trans-cyclooctene (TCO) as a ligation partner, while norbornene appears too kinetically slow for use in situ. We further show that this strategy can be applied successfully to transport a large protein into living cells. Our results validate a promising first step in achieving control over cell penetration and to use CPPs for therapeutic approaches.